Endoscopic and open decompression of median nerve in carpal tunnel = Эндоскопическая и открытая декомпрессия срединного нерва в области карпального канала - Chyrka, I. L.; Tsymbaliuk, V. I. (Journal of Education, Health and Sport, 2015)
Chyrka I. L., Tsymbaliuk V. I. Endoscopic and open decompression of median nerve in carpal tunnel = Эндоскопическая и открытая декомпрессия срединного нерва в области карпального канала. Journal of Education, Health and Sport. 2015;5(7):251-257. ISSN 2391-8306. DOI 10.5281/zenodo.19951 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A251-257 https://pbn.nauka.gov.pl/works/583796 http://dx.doi.org/10.5281/zenodo.19951 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2015. Revised 05.07.2015. Accepted: 10.07.2015. ENDOSCOPIC AND OPEN DECOMPRESSION OF MEDIAN NERVE IN CARPAL TUNNEL Эндоскопическая и открытая декомпрессия срединного нерва в области карпального канала I. L. Chyrka, V. I. Tsymbaliuk Institute of Neurosurgery named after acad. A.P. Romodanov NAMS Ukraine, Kiev, Ukraine Vinnitsa National Medical University named after N.I.Pirogov, Cathedra of Neurology and Neurosurgery, Vinnitsa, Ukraine Key words: carpal tunnel syndrome, median nerve, endoscopic decompression, open decompression. Ключевые слова: карпальный туннельный синдром, срединный нерв, эндоскопическая декомпрессия, открытая декомпрессия. Abstract The authors of the study introduced into clinical practice endoscopic decompression of median nerve in carpal tunnel. A comparative study of the effectiveness endoscopic and direct decompression of the median nerve in the carpal tunnel syndrome was done. Surgical treatment was performed in 54 patients. 28 patients included in the group of endoscopic surgery, 26 - in the open surgery group. To evaluate results of study the clinical features, the data of dynamometry, the study of discriminatory sensitivity of compressed nerve, electroneuromyography and an ultrasound scan of the median nerve in the carpal canal were used. Treatment results were evaluated 7 and 30 days after surgery. Based on the analysis of research highlighted the advantages of endoscopic and open techniques of decompression of the median nerve in patients with carpal tunnel syndrome. Резюме Авторами исследования внедрена в клиническую практику эндоскопическая методика декомпрессии срединного нерва в области карпального канала. Проведено сравнительное исследование эффективности эндоскопической и прямой декомпрессии срединного нерву при карпальном туннельном синдроме. Хирургическое вмешательство выполнено 54 пациентам. 28 пациентов вошли в группу эндоскопической хирургии, 26 – в группу открытой хирургии. Для оценки результатов использовали особенности клинической картину, данные динамометрических проб, исследование дискриминационной чувствительности в дерматоме компримированного нерва, электронейромиографию и ультразвуковое сканирование срединного нерва над и в карпальном канале. Результаты лечения оценивались на 7 и 30 сутки после проведения хирургического вмешательства. На основе анализа результатов исследования разработаны практические рекомендации и выделены преимущества эндоскопической и открытой методики декомпрессии срединного нерву у пациентов с карпальным туннельным синдромом.